2020
DOI: 10.1590/1413-812320202511.33072018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of FunFRIENDS program in prevention of anxiety in Brazilian children: a randomized controlled pilot trial

Abstract: This study aimed to evaluate the effects of the FunFRIENDS protocol on anxiety symptoms, internalizing problems and prosocial behavior in 4- to 5-year old children. Participated of this study 43 children with an allocation ratio of 1:1 between groups (Intervention Group [IG], N = 21; Control Group [CG], N = 22) from a public school in the city of Sao Paulo participated in the study. Behaviors were evaluated by using standardized questionnaires (PAS, CBCL, SDQ, SCBE) assessing the behavioral profile of the chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This program focuses on reducing anxiety symptoms and promoting protective factors against the onset of future psychopathology. Recent studies have demonstrated feasibility and positive effects of the program in Australia (Anticich et al, 2013; Barrett et al, 2015; Carlyle, 2014; Fisak et al, 2018; Pahl & Barret, 2010), Brazil (Garcia et al, 2019; Rivero et al, 2020), Mexico (Gallegos-Guajardo et al, 2020, 2013), and the Netherlands (Van der Mheen et al, 2020). Interestingly, a study conducted in Japan using Fun FRIENDS with older children found minimal effects, highlighting the limits of this program among older youth (Kato & Shimizu, 2017) and the need for research in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…This program focuses on reducing anxiety symptoms and promoting protective factors against the onset of future psychopathology. Recent studies have demonstrated feasibility and positive effects of the program in Australia (Anticich et al, 2013; Barrett et al, 2015; Carlyle, 2014; Fisak et al, 2018; Pahl & Barret, 2010), Brazil (Garcia et al, 2019; Rivero et al, 2020), Mexico (Gallegos-Guajardo et al, 2020, 2013), and the Netherlands (Van der Mheen et al, 2020). Interestingly, a study conducted in Japan using Fun FRIENDS with older children found minimal effects, highlighting the limits of this program among older youth (Kato & Shimizu, 2017) and the need for research in other countries.…”
Section: Introductionmentioning
confidence: 99%